Multi-Energy Conversion and Electromagnetic Shielding Enabled by Carbonized Polyimide/Kevlar/Graphene Oxide@ZIF-67 Bidirectional Complex Aerogel-Encapsulated Phase-Change Materials - Shi, Tao; Gao, Xing; Liu, Huan; Wang, Xiaodong (Nano-Micro Letters, 2025)
To address the limitations of conventional energy systems and optimize the energy conversion pathways and efficiency, a type of “five-in-one” multifunctional phase-change composite with magnetothermal, electrothermal, solar-thermal, and thermoelectric energy conversion and electromagnetic shielding functions is developed for multipurpose applications. Such a novel phase-change composite is fabricated by an innovative combination of paraffin wax (PW) as a phase-change material and a carbonized polyimide/Kevlar/graphene oxide@ZIF-67 complex aerogel as a supporting material. The carbonized complex aerogel exhibits a unique bidirectional porous structure with high porosity and robust skeleton to support the loading of PW. The reduced graphene oxide and CoNC resulting from high-temperature carbonization are anchored on the aerogel skeleton to generate high thermal conduction and magnetic effect, enhancing the phonon and electron transfer of the aerogel and improving its energy conversion efficiency. The phase-change composite not only exhibits excellent solar-thermal, thermoelectric, electrothermal, and magnetothermal energy conversion performance, but also achieves high electromagnetic interference shielding effectiveness of 66.2 dB in the X-band. The introduction of PW significantly improves the thermal energy-storage capacity during multi-energy conversion. The developed composite exhibits great application potential for efficient solar energy utilization, sustainable power generation, outdoor deicing, human thermal therapy, and electronic device protection. Highlights: 1 A “five-in-one” multifunctional phase-change composite is developed for magnetothermal, electrothermal, solar-thermal, and thermoelectric energy conversion and electromagnetic shielding applications. 2 The developed composite is based on an innovative combination of carbonized polyimide/Kevlar/graphene oxide@ZIF-67 complex aerogel as a supporting material and paraffin wax as a phase-change material. 3 The developed composite exhibits excellent solar-thermal, thermoelectric, electrothermal, and magnetothermal energy conversion performance along with high electromagnetic interference shielding effectiveness.